THE EFFECT OF ACCOUNTING INFORMATION ON DECISION MAKING OF MUDHARABAH AND MURABAHAH FINANCING WITH NON PERFORMING FINANCING POLICY AS MODERATING IN THE SHARIA SUMUT BANK - Malik, Imam (Asosiasi Dosen Akuntansi Indonesia, 2019)
Islamic banks are special types of banks that have finance in a century. Although they are referred to as banks, Islamic banks are built on different principles such as religious ethics and jurisprudence. In addition, they are designed for different purposes such as achieving Islamic socio-economic goals. The purpose of this study is to analyze accounting information (Curret Ratio, Short Term Mismatch Plus, Financing To Deposit Ratio, Debt To Equty Ratio, Retrun On Equity) with mudharabah and murabaha financing decisions. This research is a research that has been done by several researchers, in previous studies trying to test the relationship between accounting information and financial decision making is still not convincing. The subject of this research is accounting information that is used as a financial ratio measurement tool to see mudharabah and murabaha financing decisions at the North Sumatran Bank with 5 Branches examined, over a period of 6 years using secondary data. This study uses panel data by testing using the eviews 9 application. The results of the researchers after doing the test model, get a fixed test model, after doing the fixed test then do the classic assumption test, the results of the classic assumption test explain all normal tests. F test shows a significant value of 0,000 smaller than 0.05. The results of this F test indicate that the independent variables jointly (simultaneously) have a significant influence on the dependent variable mudharabah and murabaha financing. In terms of Curret Ratio, Short Term Mismatch Plus, Financing To Deposit Ratio, it has a negative effect on mudharabah and murabahah financing but not significantly above> 0.05. In contrast to the Debt To Equty Ratio ratio, a positive and significant effect on mudharabah and murabaha financing in the Sumut Syariah Bank 0.01 <0.05. Retrun On Equity is not a significant negative effect. Likewise, moderating Non Performing financing does not moderate one variable between (Curret Ratio, Short Term Mismatch Plus, Financing To Deposit Ratio, Debt To Equty Ratio, Retrun On Equity).